Embedded system application development for the Raspberry Pi - Wong, Wing Han (2015)
According to various studies, approximately 40 percent of the energy consumed globally is related to buildings. Artificial lighting plays a major part in the high amount of electrical energy consumed. 20 to 50 percent of the total energy consumed is due to the lighting in offices. Most importantly, in some buildings, more than 90 percent of energy consumed on lighting is wasted expense through over-illumination. By implementing automatic control of turning on and off light bases in presence detection or hourly basis, it helps to increase the energy efficiency and reduce the unnecessary energy usage. This report describes an integration approach for developing home automation control using embedded development to manage the domestic activities such as turning on and off the light bases on the presence detection. Details on the single board computer concept, proof of concept implementation which includes mechanical design, hardware design and hardware interface integration, are presented. Lastly, the test results, conclusions and recommendations for future work are described in the report.